Nanoindentation characterization of Sn-Ag-Sb/Cu substrate IMC Layer subject to thermal aging - Shualdi W.; Bais B.; Ahmad I.; Omar G.; Isnin A. (2023)
Intermetallic compound (IMC) plays great roles in connecting components to PCB boards, as well as die attach materials connecting chips to substrates. Cracks in IMC may leads to failure in an electronic product function. Therefore it is important to investigate the mechanical properties of the IMC to ensure the reliability of the solder joints. In this paper, a nanoindentation test was performed at IMCs that grow on the interface between Sn-Ag-Sb lead-free solder alloy and its Cu substrate. The test was done from planar IMC surface. Prior of that, the specimens were subjected to thermal aging process until 1500 hours at 175C to accelerate the growth of IMC. The nanotest was executed on specimens with completed aging time for 100, 200, 400, 800 and 1500 hours. Nanoindentation results in this paper show the hardness and Young modulus of IMC composition as a whole, without interpretation of hardness properties of Cu3Sn and Cu6Sn5 individually. The hardness of Sn-Ag-Sb/Cu Substrate IMC Layer is decreasing from 5.583 GPa to4.444 GPa while the Young modulus is decreasing from 106.475 GPa to 128.439 GPa. 2011 IEEE.